Next generation sequencing reveals a novel nonsense mutation in MSX1 gene related to oligodontia - Bonczek, Ondřej; Bielik, Peter; Krejčí, Přemysl; Zeman, Tomáš; Izakovičová-Hollá, Lýdie; Šoukalová, Jana; Vaněk, Jiří; Gerguri, Tereza; Balcar, Vladimir J; Šerý, Omar (PloS one, 2018)
Tooth agenesis is one of the most common craniofacial disorders in humans. More than 350 genes have been associated with teeth development. In this study, we enrolled 60 child patients (age 13 to 17) with various types of tooth agenesis. Whole gene sequences of PAX9, MSX1, AXIN2, EDA, EDAR and WNT10a genes were sequenced by next generation sequencing on the Illumina MiSeq platform. We found previously undescribed heterozygous nonsense mutation g.8177G>T (c.610G>T) in MSX1 gene in one child. Mutation was verified by Sanger sequencing. Sequencing analysis was performed in other family members of the affected child. All family members carrying g.8177G>T mutation suffered from oligodontia (missing more than 6 teeth excluding third molars). Mutation g.8177G>T leads to a stop codon (p.E204X) and premature termination of Msx1 protein translation. Based on previous in vitro experiments on mutation disrupting function of Msx1 homeodomain, we assume that the heterozygous g.8177G>T nonsense mutation affects the amount and function of Msx1 protein and leads to tooth agenesis.
Keywords: anodoncie; Family; Pedigree; rodina; rodokmen; nesmyslný kodon; High-Throughput Nucleotide Sequencing; Adolescent; malformované nehty; mladiství; molekulární modely; MSX1 Transcription Factor; Models, Molecular; lidé; ženské pohlaví; Humans; vysoce účinné nukleotidové sekvenování; Codon, Nonsense; Female; transkripční faktor MSX1; Anodontia; Nails, Malformed